A study of intention to recycle pesticide packaging among rural farmers in China based on the logistic model. (1st April 2023) - Li, Ye; Wang, Ying; Han, Xinran; Wang, Haodong; Fu, Jia
Abstract: A consequence of the improvement in China's agricultural production capacity has been increased production of pesticide packaging waste, which is a major obstacle to the sustainable development of rural areas. Although the Chinese government has made great efforts to control pollution by waste pesticide packaging, a unified recycling system has not yet been established. Therefore, determining whether farmers are willing to participate in recycling of pesticide packaging is of great relevance. This study conducted a random questionnaire survey in which 459 responses were obtained in rural areas in Liaoning, Henan, Guizhou, Anhui, Gansu, and Hunan provinces. The disorderly classification logistic model was used to analyze the individual characteristics of farmers, pesticide container sizes, perception of risk, conditions of local facilities, and awareness. The result showed that the individual characteristics of farmers and awareness had no influence of their willingness to participate in recycling, whereas container size, perception of risk, and condition of local facilities did have an influence. Container specifications have the strongest correlation with farmers' willingness to recycle, and attempts can be made to promote pesticide packaging of about 500 ml; raising farmers' awareness of environmental safety and possible health hazards, all of which can increase farmers' participation in the work. Using these results, this study proposed suggestions for pesticide container waste disposal. Attempts can be made to establish a suitable recycling model and management mechanism through the establishment of additional recycling points. Refine pesticide packaging waste recycling, collection and storage, disposal and other measures to purify the environment of origin, to achieve green agricultural development, and promote the construction of ecological civilization.